A MANAGEMENT OF PULMONAL HYPERTENSION IN CHRONIC OBSTRUCTIVE PULMONARY DISEASE - IDA BAGUS ADITYA NUGRAHA; IDA AYU PUTU PADMI DEVIANI (JURNAL KEDOKTERAN RAFLESIA, 2023)
Chronic obstructive pulmonary disease (COPD) is an obstructive pulmonary disease due to inflammatory processes of the respiratory tract and lung parenchyma. In some cases of COPD, changes in the pulmonary vessels are found which are not uncommon, causing impaired gas exchange and causing pulmonary hypertension which is associated with increased morbidity and mortality. Pulmonary hypertension is an increase in the mean pulmonary artery pressure (Pulmonary Arterial Pressure) greater than or equal to 25 mmHg at rest as assessed by a right heart catheterization procedure. Pulmonary hypertension (HP) can exacerbate the occurrence of COPD where HP patients with COPD must receive optimal COPD management according to GOLD guidelines. Pulmonary hypertension can be caused by a variety of conditions which WHO divides into five major groups. Pulmonary hypertension in patients with COPD belongs to the third group. The pathophysiology of pulmonary hypertension in patients with hypoxia or chronic lung disease is caused by tunica media hypertrophy and tunica intima proliferation leading to distal pulmonary artery obstruction. Clinical and physical symptoms in HP patients in COPD usually overlap. If HP is suspected, echocardiography is the best initial examination. Definitive diagnosis obtained through right heart catheterization. In contrast to idiopathic pulmonary hypertension, examination of the vasoreactivity of blood vessels during right heart catheterization in this group is not recommended. The goal of therapy is improvement of clinical symptoms, hemodynamic status, right ventricular function and ultimately increase in quality of life and life expectancy. Oxygen therapy is the main therapy in HP and COPD after medical therapy. Providing adequate therapy for HP with COPD is expected to provide good outcomes for patients.